Peran Taman Baca Masyarakat (TBM) terhadap Peningkatan Budaya Literasi di Masyarakat Desa Titik, Kecamatan Semen, Kabupaten Kediri - Lailatul Azizah, Siti Nur; Silviana, Willia Arum; Setyorini, Zanuarsita; Faradiba, Anggita Ayu; Falantiano, Fachrul Eza; Sulistyowati, Sulistyowati (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
The interest and reading culture of Indonesian society is still very low. The government has made various efforts to overcome this problem. One of the government's efforts is through community reading parks (TBM). Community Reading Parks (TBM) play an important role in efforts to increase literacy culture in society, especially in areas with limited access to formal education resources. This research report is entitled